Stress analysis of the Lower Riser Package (LRP) funnel when landing on the Composite Valve Block (CVB) hub of the Enhanced Vertical Deepwater Tree (EVDT) - Goh, Samuel Yuheng. (2013)
The Emergency Disconnect Package (EDP) / Lower Riser Package (LRP) stack lands on the Enhanced Vertical Deepwater Tree (EVDT) through the top drive of the rig. This process is facilitated by the use of a guide funnel to ensure that the Composite Valve Block (CVB) hub of the EVDT interfaces correctly with the LRP.